Visual tracking and its relationship to dynamic visual acuity among national youth foil fencing team athletes - Oudah, I. G.; Jari, H. S.; Taih, H. S.; Sameer, A. H. (Modern Sport, 2025)
The significance of this study lies in its focus on the relationship between visual tracking and dynamic visual acuity, both regarded as essential perceptual abilities influencing technical and dynamic performance in foil fencing. This supports coaches and specialists in designing effective training units to improve players' visual and motor efficiency. Given the interactive, fast-paced nature of the sport-which demands instantaneous reactions and high precision in thrusting-there is a need to determine the impact of visual tracking on performance quality. The research problem arose from the authors' observation of the limited attention to visual perceptual aspects in preparation programs, despite their role as key determinants of successful performance. The study aimed to assess visual tracking and dynamic visual acuity levels among youth foil fencers and explore the correlation between them. A descriptive methodology using a correlational approach was adopted. The sample included ten athletes from the national youth foil fencing team, aged 17 to 19 years. Specialized tests measured visual tracking and dynamic visual acuity. Data were collected during a defined period using precise instruments, and results were analyzed using Pearson's simple correlation coefficient. The findings revealed a strong, statistically significant positive correlation between visual tracking and dynamic visual acuity (r = 0.752), indicating that efficient visual tracking contributes to improving thrust accuracy during fencing bouts. The study concluded that developing visual perceptual skills-particularly visual tracking-is fundamental to enhancing technical performance in fencing. It is recommended that visual perception training be integrated into preparation stages and that future studies include various age groups and skill levels. and this achieves one of the sustainable development goals of the United Nations in Iraq which is (Quality Education)